MPPP-HARQ: A HARQ Scheme with Multi-Packet Retransmission and Packet-wise Polarization - Jin, Shan; Zhang, Zhaoyang; Shang, Yuzhou; Wang, Jue (IEEE Vehicular Technology Conference, 2021)
Existing hybrid automatic repeat request (HARQ) schemes are mainly designed at bit-level, in which the bits with lower reliability are re-encoded and then re-transmitted. However, this may lead to complicated and nonflexible bit-wise joint design among all the re-transmitted packets and introduce extra decoding latency. In this paper, we propose a novel HARQ scheme with multi-packet retransmission and packet-wise polarization, MPPP-HARQ, which simply retransmits the polar coded version of the failed packets as well as the new information packets instead of any specific part of them, so as to avoid all complicated and trivial inner-bit manipulation and greatly reduce the system complexity. Just like the bit-wise polarization, the packet-wise polarization is realized by proper modulo two addition among packets. By proper combination of multiple packets at each retransmission, we can reliably recover all the received packets at the decoder using a joint iterative decoding algorithm. Simulation results show that compared to the traditional HARQ protocol, MPPP-HARQ achieves superior performance and obtains a significant performance gain in terms of throughput and error rate.